PHONETIC AND SYNTACTIC LANGUAGE DEVELOPMENT OF 3 YEARS OLD CHILDHOOD - Shakila, Ika; Alyani, Elsa; Wulandari, Siti; Nargis (Media Inovasi Pendidikan dan Publikasi, 2024)
This research analyzes the phonetic and syntactic development of language in 3 year old children using qualitative descriptive methods. By observing and recording children's verbal interactions over several weeks, the aim of this study was to capture the details of early language acquisition. This analysis focuses on pronunciation patterns, vocabulary growth, and the formation of syntactically correct sentences. Researchers noted that children showed significant progress in phonetic articulation, with marked improvements in clarity of consonant and vowel sounds. Syntactically, children show increasing ability to form simple sentences, use basic grammatical structures, and arrange words in the correct order. This research provides valuable insight into typical language development milestones in children of this age, emphasizing the importance of a supportive and interactive linguistic environment.